Strategies, practices, and challenges in enhancing quality assurance in qualitative biomedical research: A multi-method study protocol - Hamidreza Khankeh; Mohammad Saatchi; Mahdieh Motie; Shima Shirozhan; Ulrich Dirnagl (Journal of Research Development in Nursing and Midwifery)
Background: The qualitative research paradigm is crucial for understanding complex human phenomena, making credibility essential for its findings. Challenges in applying quality assessment criteria and promoting responsible practices in biomedical research underscore the need to review strategies, practices, and challenges in evaluating the quality of qualitative research. This protocol aims to support a multi-method study that develops evidence-informed, comprehensive, and practical recommendations to enhance quality assurance in qualitative research within the biomedical field. Methods: This multi-method study protocol consists of three phases: a systematic scoping review, qualitative content analysis, and a Delphi survey. The scoping review will follow Arksey and O’Malley’s five-step approach, using relevant keywords to guide a systematic search across databases such as PubMed, CINAHL, Web of Science, Scopus, and Embase, with no time restrictions. Qualitative content analysis will follow Graneheim and Lundman’s (2004) method. Purposeful sampling will be used to select experts in qualitative research. Semi-structured interviews will collect their experiences in evaluating qualitative research quality. Based on the review and interview findings, comprehensive, evidence-informed, and practical recommendations within the biomedical field will be developed and further refined using the Delphi method. Conclusion: This study aims to critically examine quality achievement and evaluation in the qualitative paradigm and identify challenges, practices, and strategies through a review of existing evidence, focusing on related experiences and perceptions. The study also seeks to address gaps and controversies in the literature using qualitative content analysis. Ultimately, the goal is to develop comprehensive, evidence-informed, and practical recommendations to enhance quality assurance in qualitative research.